2020
DOI: 10.1016/j.nucmedbio.2020.09.002
|View full text |Cite
|
Sign up to set email alerts
|

A kit formulation for the preparation of [89Zr]Zr(oxinate)4 for PET cell tracking: White blood cell labelling and comparison with [111In]In(oxinate)3

Abstract: Background Advances in immunology and cell-based therapies are creating a need to track individual cell types, such as immune cells (neutrophils, eosinophils, chimeric antigen receptor (CAR) T cells, etc.) and stem cells. As the fate of administered cells remains largely unknown, nuclear imaging could determine the migration and survival of cells in patients. [ 89 Zr]Zr(oxinate) 4 , or [ 89 Zr]Zr-oxine, is a radiotrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
0
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(50 citation statements)
references
References 46 publications
3
45
0
2
Order By: Relevance
“…However, a significant increase in the cell cycle arrest and apoptosis was detected. Man et al demonstrated that significant DNA damage is evident in white blood cells labelled with [ 89 Zr]Zr-oxine at 32.9 kBq/10 6 cells [24]. Patrick et al established that the majority of DNA damage is repaired at the 7-day time point [42].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, a significant increase in the cell cycle arrest and apoptosis was detected. Man et al demonstrated that significant DNA damage is evident in white blood cells labelled with [ 89 Zr]Zr-oxine at 32.9 kBq/10 6 cells [24]. Patrick et al established that the majority of DNA damage is repaired at the 7-day time point [42].…”
Section: Discussionmentioning
confidence: 99%
“…Several parameters were investigated to improve the radiochemical conversion (RCC) from the original protocol [16,[24][25][26], as well as to minimise the timeframe of radioactive exposure. See supplementary.…”
Section: Optimization Of [ 89 Zr]zr-oxine Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…This allows imaging of cell migration for as much as 1-2 weeks, since the radionuclide is largely retained by the labelled cells. A simplified, good manufacturing practice (GMP)-compatible kit-based method of producing the 89 Zr-oxine complex has been reported recently, [60] greatly enhancing the opportunity for wider use in clinical trials of cell-based therapy. An alternative approach to cell labelling is by conjugation of DFO-based zirconium-89 chelates [61] or iodine-124-prosthetic groups [62] (Fig.…”
Section: Cell Trackingmentioning
confidence: 99%
“…Oxinates of the transition radiometals gallium-68, zirconium-89 and indium-111 ([ 68 Ga]Ga(oxinate) 3 , [ 89 Zr]Zr(oxinate) 4 , [ 111 In]In(oxinate) 3 ) are highly lipophilic molecules that can be incorporated into lipid-bilayered nanovesicles (liposomes) and living cells under neutral conditions. Using this mechanism, more recent studies disseminated [ 89 Zr]Zr(oxinate) 4 -related cell tracing by applying various labeling protocols from 60% to 97% labeling efficiency of the prelabeled oxinate [2][3][4][5][6] and complex liposome labeling by combining this method with a liposome-incorporated bifunctional chelator [7].…”
Section: Introductionmentioning
confidence: 99%